2015
DOI: 10.1074/mcp.m114.045658
|View full text |Cite
|
Sign up to set email alerts
|

BioID-based Identification of Skp Cullin F-box (SCF)β-TrCP1/2 E3 Ligase Substrates*

Abstract: The identification of ubiquitin E3 ligase substrates has been challenging, due in part to low-affinity, transient interactions, the rapid degradation of targets and the inability to identify proteins from poorly soluble cellular compartments. SCF ␤-TrCP1 and SCF ␤-TrCP2 are well-studied ubiquitin E3 ligases that target substrates for proteasomal degradation, and play important roles in Wnt, Hippo, and NFB signaling. Combining 26S proteasome inhibitor (MG132) treatment with proximity-dependent biotin labeling (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
138
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 166 publications
(142 citation statements)
references
References 58 publications
4
138
0
Order By: Relevance
“…Methodologically, our analysis complements previous work that relied on alternative approaches. The major advantage of in situ proximity ligation is that it is done in living cells and thus preserves all subcellular structures, protein concentrations, and regulatory networks (Hung et al , 2014; Coyaud et al , 2015), while several previous studies relied on protein extraction or permeabilized cells. Nevertheless, cross‐validation against such previous data showed that similar set of cargos are identified (Kimura et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methodologically, our analysis complements previous work that relied on alternative approaches. The major advantage of in situ proximity ligation is that it is done in living cells and thus preserves all subcellular structures, protein concentrations, and regulatory networks (Hung et al , 2014; Coyaud et al , 2015), while several previous studies relied on protein extraction or permeabilized cells. Nevertheless, cross‐validation against such previous data showed that similar set of cargos are identified (Kimura et al , 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The AP was performed as previously described (Coyaud et al , 2015). Instead of a protease inhibitor mixture, 1 mg/ml aprotinin and 0.5 mg/ml leupeptin was used.…”
Section: Methodsmentioning
confidence: 99%
“…Hence, it is possible that HWS contributes to the miRNA pathway through a protein not yet described in this contextthat the interaction with an already known factor is weak or transient, as described for other F-box proteins (Earley et al, 2010;Coyaud et al, 2015)-or that the concentration of the interactor in entire leaves is low and therefore not detectable by our approach. Although we are confident that the F-box domain is important for HWS's function in the miRNA context, its mode of action and interaction(s) with miRNA factors remain to be determined.…”
Section: Genetic Interactions With Other Mirna Factorsmentioning
confidence: 97%
“…If a larger labeling radius is desired, for example to capture more constituents within a large protein complex, it can be increased by insertion of flexible linkers between the bait and the ligase [23]. BioID also captures protein associations over a period of time and independent of stable interactions, making it an effective approach in identifying novel substrates of proteins with dynamic and transient protein associations such as the E3 ubiquitin ligase, β-TrCP1 [24]. …”
Section: Biotin Ligase-based Methods For Proximity Labelingmentioning
confidence: 99%